Perilaku Produsen Pelaku Usaha Rias Pengantin - Putri Hestiningrum; Dwi Yuli Rakhmawati; Siti Muhimatul Khoiroh (Inspirasi Nusantara, 2023)
This study discusses how the behavior of bridal makeup entrepreneurs in running their businesses. The bridal makeup business is one type of business that is engaged in services. The bridal makeup business sector relies on the creative abilities, skills, and talents of business actors in creating service selling points. The existence of bridal make-up services functions as a complement to the event of weddings and community cultural events in Malang Regency and is full of customs. To deal with fluctuations in the business climate that are influenced by customs, businessmen have different strategies, resulting in differences in turnover between businessmen. Using a qualitative approach, researchers conducted in-depth interviews with bridal makeup artists in Malang Regency to obtain primary data. The research data were analyzed using the Miles and Huberman model, and to test the validity of the data, the researcher triangulated the data. The results of the study show that there is vertical and horizontal integration behavior between bridal makeup businessmen with photographers, jasmine craftsmen, and other bridal makeup artists in running a business; bridal makeup businessmen discriminate against prices based on consumer groups; and bridal makeup businessmen carry out imitative strategies in developing services.